HUBUNGAN KECANDUAN BERMAIN GAME ONLINE DENGAN MOTIVASI BELAJAR PADA ANAK USIA 10-12 TAHUN - Reza Indra Wiguna; H Menap; Deby Ayu Alandari; Lalu Hersika Asmawariza (Jurnal Surya Muda, 2020)
Online gaming is one of the technology that has influence in many communities, including children. Excessive online gaming activity can bring a negative impact on children. And the negative impact referred to in this study is the reduced motivation for learning in children. The population in this study was 10-12 years of age at SDN 2 Leneng Praya as many as 51 students in which the study used a tekhnik with Purposive Sampling determination using the inclusion and exclusion criteria for Population as respondents or samples. The research method used is Cross Sectional with a quantitative research type, and the data analysis method used is a test of Sperman Rank. The data presented in this study used the primary data through the questionnaire. The results showed that the addiction to playing online games had a significant connection to the learning motivation of the child being demonstrated from the Sperman Rank test of motivational learning of Nilai P < 0.003 which is smaller than 0.05.